Sustainable GSM-Based Remote Switching System Using Conventional Mobile Phones Without Microcontroller for Low-Cost Automation Applications - Ahmad Saddam Habibullah; Sutan Ali Sianipar (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
The development of telecommunications-based control systems has become an alternative solution in home automation and small industries, especially in areas with limited internet access. This study aims to design and test a telephone-based electrical equipment control module that utilizes conventional mobile phones as an activation medium without the aid of a microcontroller. This system consists of a tuner block, a three-stage Darlington amplifier, a Schmitt Trigger with an optocoupler, a 555 IC multivibrator, and a relay as the main actuator. Test results show that the power supply circuit is capable of maintaining voltage stability of ±0.1 V on the 5V and 9V lines, while the tuner successfully detects electromagnetic signals with a fairly stable output voltage of 0.05–0.98 V to trigger the signal amplifier. The multivibrator circuit showed a consistent flip-flop response to logic pulses from the tuner, while the relay was able to operate mechanically in two stable conditions (ON/OFF). These findings show that analog signals from mobile phones can be effectively integrated with pure electronic circuits to produce a reliable, cost-effective, and environmentally friendly remote control system. The advantage of this research lies in the approach of reusing low-end GSM technology for internet-free automation that supports the principles of circular economy and electronic waste reduction.